READING, INTERPRETATION AND TRANSCREATION: CONCEPTIONS OF TRANSLATION AMONG GERMAN PHILOSOPHY STUDENTS - Bontempi Pizzi, Maria Claudia; Faria Rozenfeld, Cibele Cecilio de [UNESP] (Unesp-faculdade Ciencias & Letras, 2015)
The interest in learning German is often triggered by the desire and need of reading German texts in their source languages, a fact that is commonly observed among Philosophy students. This paper aims at presenting an e-learning German course for Philosophy students who sought linguistic enhancement in order to better understand texts of the area in their source language and focused on different conceptions of translation. To this end, we describe the course in detail and analyze the discussions held in four online forums, seeking to identify the notions of translation imbued among the course participants. The results indicate, on one hand, the validity of e-learning courses for German students with specific demands such as understanding and translation of philosophical texts. On the other hand, the considerations here presented show different conceptions of the act of translation. Our goal is to contribute to the field of translation studies, as well as highlighting an interesting way to be followed in German as a foreign language teaching and learning.
Keywords: German as a foreign language teaching and learning; German for Specific Purposes for Philosophy readers; Translation; E-learning German courses